# Problem of the Week #88 - December 2nd, 2013

Status
Not open for further replies.

#### Chris L T521

##### Well-known member
Staff member
Thanks again to those who participated in last week's POTW! Here's this week's problem!

-----

Problem: Suppose $f$ is a differentiable function of one variable. Show that all tangent planes to the surface $z=xf(y/x)$ intersect in a common point.

-----

#### Chris L T521

##### Well-known member
Staff member
This week's problem was correctly answered by MarkFL. You can find his solution below.

We are given:

$$\displaystyle z(x,y)=xf\left(\frac{y}{x} \right)$$

Let us the define:

$$\displaystyle F(x,y,z)=xf\left(\frac{y}{x} \right)-z$$

Thus, a point $\left(x_0,y_0,z_0 \right)$ is on the graph of $$\displaystyle z(x,y)=xf\left(\frac{y}{x} \right)$$ iff it is also on the level surface $F(x,y,z)=0$. This follows from $$\displaystyle F\left(x_0,y_0,z_0 \right)=x_0f\left(\frac{y_0}{x_0} \right)-z_0=0$$.

Next, we may utilize the following theorem:

Equation of Tangent Plane

Let $P\left(x_0,y_0,z_0 \right)$ be a point on the graph of $F(x,y,z)=c$ where $\nabla F\ne0$. Then an equation of the tangent plane at $P$ is:

$$\displaystyle F_x\left(x_0,y_0,z_0 \right)\left(x-x_0 \right)+F_y\left(x_0,y_0,z_0 \right)\left(y-y_0 \right)+F_z\left(x_0,y_0,z_0 \right)\left(z-z_0 \right)=0$$

Computing the required partials, we find:

$$\displaystyle F_x(x,y,z)=xf'\left(\frac{y}{x} \right)\left(-\frac{y}{x^2} \right)+f\left(\frac{y}{x} \right)=f\left(\frac{y}{x} \right)-\frac{y}{x}f'\left(\frac{y}{x} \right)$$

$$\displaystyle F_y(x,y,z)=xf'\left(\frac{y}{x} \right)\left(\frac{1}{x} \right)=f'\left(\frac{y}{x} \right)$$

$$\displaystyle F_z(x,y,z)=-1$$

Using the above theorem, we then find the equation of the tangent plant at $P$ is:

$$\displaystyle \left(f\left(\frac{y_0}{x_0} \right)-\frac{y_0}{x_0}f'\left(\frac{y_0}{x_0} \right) \right)\left(x-x_0 \right)+\left(f'\left(\frac{y_0}{x_0} \right) \right)\left(y-y_0 \right)+(-1)\left(z-z_0 \right)=0$$

Distributing and rearranging, we obtain:

$$\displaystyle ]\left(f\left(\frac{y_0}{x_0} \right)-\frac{y_0}{x_0}f'\left(\frac{y_0}{x_0} \right) \right)x+\left(f'\left(\frac{y_0}{x_0} \right) \right)y-z-\left(x_0f\left(\frac{y_0}{x_0} \right)-z_0 \right)=0$$

Now, given $$\displaystyle F\left(x_0,y_0,z_0 \right)=x_0f\left(\frac{y_0}{x_0} \right)-z_0=0$$, this reduces to:

$$\displaystyle ]\left(f\left(\frac{y_0}{x_0} \right)-\frac{y_0}{x_0}f'\left(\frac{y_0}{x_0} \right) \right)x+\left(f'\left(\frac{y_0}{x_0} \right) \right)y-z=0$$

Observing that all planes given by $ax+by+cz=0$ pass through the origin, we therefore find that all of the planes tangent to $z$ must have the origin as a common point.

Status
Not open for further replies.